Wolność tłumacza w procesie lokalizacji gier wideo na przykładzie Final Fantasy XV - Witczak, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Video game localization is a process that is strongly focused on the target audience. Its aim is to adapt the game content to the linguistic and cultural needs and requirements of the market other than the primary one. A well-made localization cannot negatively affect the gameplay experience and the player’s sense of immersion. Therefore, when translating in-game text, translators can use strategies and techniques known from other types of translations. The aim of this article is to show how the use of transcreation in the localization process can influence the reception of a game. An attempt is made to answer the question of whether the freedom to interfere with the original content, which this translation strategy gives the translator, is justified. For this purpose, the specificity of video game localization is briefly presented, and various concepts and theories from the field of translation theory are used. Final Fantasy XV, released in 2016 by Square Enix, was selected as the subject of the analysis.